The Effect of Liquidity and Return on Capital on Profitability : Study of Cigarette Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Debby Husna Gusrina; Bulan Tati Fitria (Jurnal Computech & Bisnis (e-Journal), 2023)
The researchers undertook the study to examine the influence of the Current Ratio and Debt-to-Equity Ratio on the Net Profit Margins of Cigarette Sub Sector Manufacturing Companies that are listed on the Indonesia Stock Exchange during the period spanning from 2016 to 2020. The study utilized a descriptive verification methodology. The study employed a statistical methodology of multiple linear regression analysis, utilizing the IBM SPSS Statistics 25.0 software program for Windows. The research employed a sample of 20 financial statements procured from the cigarette sub-sector manufacturing firms listed on the Indonesian stock exchange between the years 2016 and 2020. The present study's results indicate that the Current Ratio and Debt-to-Equity Ratio of cigarette sub-sector manufacturing firms enlisted on the Indonesia stock exchange between 2016 and 2020 significantly impact Net Profit Margin.